2006
DOI: 10.1158/1078-0432.ccr-05-2290
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Pomegranate Juice for Men with Rising Prostate-Specific Antigen following Surgery or Radiation for Prostate Cancer

Abstract: Purpose: Phytochemicals in plants may have cancer preventive benefits through antioxidation and via gene-nutrient interactions. We sought to determine the effects of pomegranate juice (a major source of antioxidants) consumption on prostate-specific antigen (PSA) progression in men with a rising PSA following primary therapy. Experimental Design: A phase II, Simon two-stage clinical trial for men with rising PSA after surgery or radiotherapy was conducted. Eligible patients had a detectable PSA >0.2 and <5 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
287
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(297 citation statements)
references
References 63 publications
3
287
0
7
Order By: Relevance
“…The potent anti-proliferative activities of the non-edible pomegranate extracts have been attributed to the high amount of phenolics present in the extracts [30,31]. Literature abounds in examples of the anti-proliferative and anticancer effect of pomegranate fruit and juice, all of which have been attributed to the high level of phenolic compounds present [13,16,20,23,[32][33][34][35][36][37][38]. Among the different mechanisms of action involved, plant phenolics exert chemopreventive activity via its antioxidative potential [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potent anti-proliferative activities of the non-edible pomegranate extracts have been attributed to the high amount of phenolics present in the extracts [30,31]. Literature abounds in examples of the anti-proliferative and anticancer effect of pomegranate fruit and juice, all of which have been attributed to the high level of phenolic compounds present [13,16,20,23,[32][33][34][35][36][37][38]. Among the different mechanisms of action involved, plant phenolics exert chemopreventive activity via its antioxidative potential [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate-derived ellagitannins showed in vitro anti-proliferative and anti-aromatase activity in breast cancer cells [13], while pomegranate juice consumption revealed a significant prolongation of prostatespecific antigen doubling time, in both an initial phase II clinical trial in patient with prostate cancer [20] and a randomized phase II study [21]. Raw pomegranate peel extract offers selective cytotoxic activity against promyelocytic (HL60) cell lines and immune-stimulatory effect in peripheral blood mononuclear cells [22].…”
Section: Introductionmentioning
confidence: 99%
“…Total prostate specific antigen (PSA) did not change, and men with symptomatic benign prostatic hyperplasia reported symptom reduction. Pomegranate juice (8 oz of concentrate, POM Wonderful variety), when given to men with a rising PSA following surgery or radiation, increased the mean PSA-doubling time from 15 months to 54 months (P < .001) without reports of adverse events [197]. When given a dietary supplement containing soy, lycopene, silymarin, and antioxidants (formulary details not given) following surgery or radiation for 10 weeks, 49 men showed an increase of PSAdoubling time from 445 days to 1,150 days, along with significant decreases in PSA slope (P ¼ .03) [198].…”
Section: Treatment Of Pre-cancerous or Specific Lesionsmentioning
confidence: 99%
“…Increased PSA-doubling time [197] Soy in complex formula in prostate cancer patients with rising PSA after radiation or surgery…”
Section: Grifola Umbellatae In Bladder Cancermentioning
confidence: 99%
“…For example, pomegranate has been found to possess well-documented cancer chemopreventive and chemotherapeutic effects against prostate cancer [10][11][12][13]. The results of a Phase II clinical study of patients with rising prostate-specific antigen (PSA) levels following surgery or radiation for prostate cancer demonstrated that pomegranate juice produced statistically significant prolongation of PSA doubling times, suggesting that pomegranate consumption may retard prostate cancer progression [14].Despite numerous published results of in silico, in vitro and in vivo studies of pomegranate, several questions remain, including which components of this dietary agent are responsible for these anti-cancer activities and by what mechanism do they actually suppress cancers. Analysis of the electronic properties of 101 pomegranate ingredients revealed that nearly 50% of these compounds represent potentially carcinostatic substances with strong electron-acceptor properties.…”
mentioning
confidence: 99%